Investigation of production planning for environmental sustainability improvement in polymer LPBF - Wang, Han (2024)
Additive Manufacturing (AM), also known as 3D printing, refers to a family of manufacturing technologies that use a layer-by-layer approach to converting digital models into physical components. The adoption of AM has offered significant sustainability benefits such as improved resource efficiency, extended product life, and reconfigured value chains. However, despite these prospective benefits, the full potential of the sustainable aspects of AM has not been explored, due to a lack of knowledge regarding environmental sustainability improvement in AM.